MOBILE AMBIENT CALCULUS WITHIN INSERTION MODELING SYSTEM (Journal of Information Technologies in Education (ITE), 2010)
This article is focused on the Insertional Modeling System developed by A.A. Letichevsky of the department 100/105 of the Glushkov Institute of Cybernetics, National Academy of Science of Ukraine, Kyiv, Ukraine. Insertion Modeling System (IMS)[1] is built on the Algebraic Programming System (APS) that also was developed by A.A. Letichevsky in 1987. On the way of implementation of ambient calculus – a process calculus devised by Luca Cardelli and Andrew D. Gordon in 1998, and used to describe and theorize about concurrent systems that include mobility.[6] In this article we are going to discuss the constructing of the framework for mobile ambients using the Insertion Modeling System.
Keywords: process calculi; ambient calculus; insertion modeling